E-Government Dalam Pencatatan Stunting Melalui Aplikasi E-Penting di Puskesmas Cigondewah - Patna Akbar Pangestu; Endang Rahmawati; Salsa Bilkis Kuds; Ivan Darmawan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article discusses the implementation of the e-Penting application in recording and reducing stunting rates in Bandung City, specifically at the Cigondewah Health Center. Stunting, which occurs in the first 1,000 days of a child's life, has long-term impacts on a child's health and development. The Bandung City Government has launched several innovations, including the e-Penting application, to address the stunting issue. The e-Penting application is the main focus of efforts to reduce stunting at the Cigondewah Health Center. Full support from the government, cross-sector coordination, and regeneration are key factors in the implementation of this application. This article also discusses the concept of e-Government as a supporter of democratic, transparent, and accountable government. The research method was conducted using an ethnographic approach, with the selection of informants through purposive sampling technique. Data were collected through in-depth interviews and non-participant observation. Data analysis adopted the Miles and Huberman model, which involved data reduction, data presentation, and conclusion drawing. The results show that although the e-Penting application is considered a positive step, there are still barriers, such as the low level of education and public awareness, as well as technical issues such as data synchronization and long inputting times. More intensive socialisation and an integrated approach with the community are needed to maximise the benefits of this application in addressing the problem.